Periodic Solutions for a Prescribed Mean Curvature Equation with Multiple Delays - Shiping Lu; Ming Lu (Journal of Applied Mathematics)
We study the existence of periodic solutions for the one-dimensional prescribed mean curvature delay equation (d/dt)(x'(t)/1+x't2) +∑i=1naitgxt-τit=pt. By using Mawhin's continuation theorem, a new result is obtained. Furthermore, the nonexistence of periodic solution for the equation is investigated as well.